Association of imputed prostate cancer transcriptome with disease risk reveals novel mechanisms - Nima C. Emami (Nature Portfolio, 2019)
In prostate cancer, investigating aberrant gene expression may shed light on disease etiology. Here, the authors imputed expression transcriptome-wide for 233,955 European ancestry men, discovering and replicating the associations between prostatic expression for select genes and prostate cancer risk, including the highly prevalent gene fusion partner TMPRSS2. The authors furthermore integrate diverse functional genomic datasets to interpret the epigenetic mechanisms by which the implicated risk variants and genes modulate disease risk.